2019
DOI: 10.3390/act8020030
|View full text |Cite
|
Sign up to set email alerts
|

Insect Muscular Tissue-Powered Swimming Robot

Abstract: Bio-actuators that use insect muscular tissue have attracted attention from researchers worldwide because of their small size, self-motive property, self-repairer ability, robustness, and the need for less environment management than mammalian cells. To demonstrate the potential of insect muscular tissue for use as bio-actuators, three types of these robots, a pillar actuator, a walker, and a twizzer, have been designed and fabricated. However, a model of an insect muscular tissue-powered swimming robot that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Xi et al [50] first proposed a biological robot in 2005, which opened a Pandora's box and triggered rapid developments in this field for the next 15 years. According to biological composition, biological driving sources can be roughly divided into five categories: mammalian primary cells [51][52][53][54][55], mammalian cell lines (mainly cardiomyocytes and skeletal muscle cells) [14,[56][57][58][59], insect dorsal vascular tissue (DV tissues) [60][61][62][63], microorganisms [64][65][66][67][68] and others (sperm, T cells, etc.) [69][70][71][72][73] (shown in Fig.…”
Section: Living Driving Sources Used For Biohybrid Robotsmentioning
confidence: 99%
See 3 more Smart Citations
“…Xi et al [50] first proposed a biological robot in 2005, which opened a Pandora's box and triggered rapid developments in this field for the next 15 years. According to biological composition, biological driving sources can be roughly divided into five categories: mammalian primary cells [51][52][53][54][55], mammalian cell lines (mainly cardiomyocytes and skeletal muscle cells) [14,[56][57][58][59], insect dorsal vascular tissue (DV tissues) [60][61][62][63], microorganisms [64][65][66][67][68] and others (sperm, T cells, etc.) [69][70][71][72][73] (shown in Fig.…”
Section: Living Driving Sources Used For Biohybrid Robotsmentioning
confidence: 99%
“…In 2019, Morishima et al proposed a swimmer prototype driven by DV tissue [62] (shown in Fig. 4b) that reaches an average swimming speed of 11.7 μm/s.…”
Section: Insect Dorsal Vessel (Dv) Tissuementioning
confidence: 99%
See 2 more Smart Citations
“…Compared to state-of-the-art artificial actuators, natural muscle has several distinguishing and desirable advantages, such as its high-energy conversion efficiency, its independency from electrical or fossil fuel energy supplies, its softness and flexibility, and its capability for self-repair [3]. Many muscle-actuated devices have been reported in the past decade such as pumping devices [4,5], manipulators [6,7], crawling robots [8][9][10], and swimming robots [11][12][13][14]. Studies on biohybrid devices have been summarized in several recently published review articles [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%